Pavilions, pop-ups and parasols : the impact of real and virtual meeting on physical space - Van Schaik, Leon; Watson, Fleur (Architectural design (London, England : 1971) ;, 2015)
Contributors: Rob Bevan, Peter Bishop, Pia Ednie-Brown, RoanChing Yueh, Beatrice Galillee, Dan Hill, Martyn Hook, Minsuk Cho, Andrea Kahn, Felicity Scott and Akira Suzuki. Contributing Architects: Alisa Andrasek/Biothing, PeterCook/CRAB Studio, CJ Lim/Studio 8, Tom Holbrook/5thStudio, Matthias Hollwich/HKWN, Mamou-Mani Architects and Benedetta Tagliabue/EMBT.